Reconstruction of Ramus-Condyle Unit with Two Rib Grafts: Report of a Case - Dehghanpou Barouj, Mehrdad; Mirmohammad Sadeghi, Hassan; Bakhshaei, Pedram (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: Ramus-condyle unit (RCU) reconstruction is one of most challenging procedures in maxillofacial surgery. Autologous graft, custom made prosthesis and transport disc distraction are some treatment options. Case Report: In this study, we reported a mandibular DF in a 9-year-old child with condylar involvement. Our treatment plan was segmental resection and reconstructed RCU with 2 rib grafts. Results: After one year of follow-up, there is no evidence of recurrence. Mandible has symmetrical appearance and normal centric and eccentric movement. Conclusion: Rib graft is recommended for RCU reconstruction, especially in children in the growing stage.